Injury of the Spinothalamic Tract Following Whiplash Injury: A Diffusion Tensor Tractography Study - Sung Ho Jang; Kyong Kim; You Sung Seo (Journal of Integrative Neuroscience, 2023)
Objectives: Using diffusion tensor tractography (DTT), we demonstrated the spinothalamic tract (STT) injury in patients with central pain following whiplash injury. Our primary hypothesis is that fractional anisotropy (FA) and tract volume (TV) of the STT in injured people differ from non-injured people. Our secondary hypothesis is that the direction of the collision results in a different type of injury. Methods: Nineteen central pain patients following whiplash injury and 19 normal control subjects were recruited. The STT was reconstructed by the DTT, the FA and TV of the STT were measured. In addition, different characteristics of the STT injury according to the collision direction were investigated. Results: The FA value did not differ significantly between the patient and control groups (p > 0.05). However, the significantly lower value of the TV was observed in patient group than the control group (p < 0.05). The onset of central pain was significantly delayed (13.5 days) in patients who were involved in a frontal collision, compared to patients with rear-end collision (0.6 days) (p < 0.05). In contrast, the Visual Analogue Scale was higher in the patients with rear-end collision (p < 0.05). Conclusions: We found the STT injury mild traumatic brain injury (TBI) who suffered central pain after whiplash injury, using DTT. In addition, we demonstrated different characteristics of the STT injury according to the collision direction. We believe that injury of the STT would be usefully detected by DTT following whiplash injury.